Non-violence and the French Revolution political demonstrations in Paris, 1787-1795 - Alpaugh, Micah (Cambridge University Press, 2015)
Historians of the French Revolution have traditionally emphasised the centrality of violence to revolutionary protest. However, Micah Alpaugh reveals instead the surprising prevalence of non-violent tactics to demonstrate that much of the popular action taken in revolutionary Paris was not in fact violent. Tracing the origins of the political demonstration to the French Revolutionary period, he reveals how Parisian protesters typically tried to avoid violence, conducting campaigns predominantly through peaceful marches, petitions, banquets and mass-meetings, which only rarely escalated to physical force in their stand-offs with authorities. Out of over 750 events, no more than twelve percent appear to have resulted in physical violence at any stage. Rewriting the political history of the people of Paris, Non-Violence and the French Revolution sheds new light on our understanding of Revolutionary France to show that revolutionary sans-culottes played a pivotal role in developing the democratically oriented protest techniques still used today